Gravity Models Estimation for Saudi Arabia Kingdom Export to Iraq and From Iraq Export to Saudi Arabia Kingdom (My country has oil resources): (An Econometrics Study for period 1990-2020) - Jafaar, Mhamed Radhi; Al-Ethary, Adnan Muhammad (Journal of Ecohumanism, 2024)
The foreign trade of any country in the world depends on the strength of exports of goods and services to other countries, and most of the intra-trade between these countries depends on the factors of gravity between them. When these variables or factors are strong, intra-trade is also strong, and this relationship can be investigated by estimating the gravity model, which depends on These variables give precise details about which variables are more effective in intra-state trade, and from this our study came to estimate the attractiveness models for each of the Kingdom’s exports. Saudi Arabia to Iraq and Iraq’s exports to the Kingdom of Saudi Arabia. The research aims to estimate these models and test them with various statistical and standard tests using quantitative methods, represented by econometrics, to achieve the goals. The research reached several results that led to knowing which of the gravity variables has a strong influence in both countries of the sample. The addition provided by Saudi Arabia’s exports to Iraq is weak, which does not affect the increase in national income and thus the increase in social welfare. Hence, we note the negativity of this variable, while the variable of the annual growth rate of the Iraqi gross domestic product Iq.GDP.Grji showed a successful relationship with the hypotheses. The theory has a positive relationship, which shows the effect of population on the increase in Saudi exports to Iraq due to the increase in demand as a result of the increase in population. Despite the weakness of the parameter, it has a strong effect. While the relationship of the time variable “Years” showed its negative relationship with Saudi exports to Iraq, and this from the economic point of view is contrary to the theoretical assumptions only. Its relationship is correct because the period studied included two wars: the Gulf War, the American occupation of Iraq, and the UN sanctions that were imposed on Iraq, which linked Iraqi imports to UN approval.. While the results of the gravity model for Iraqi exports to Saudi Arabia showed a positive relationship with Iraqi exports to Saudi Arabia, which indicates their agreement with the assumptions of economic theory and with a strong effect, while both the annual growth rate variable of the gross domestic product S.GDP.Grij and the time variable Years showed their negative relationship with Iraqi exports. Contrary to the assumptions of economic theory.